2011
DOI: 10.1002/lt.22339
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of orthotopic liver transplantation for hepatic sarcoidosis: An analysis of the United Network for organ sharing/organ Procurement and Transplantation Network data files for a comparative study with cholestatic liver diseases

Abstract: Hepatic sarcoidosis is a rare indication for liver transplantation. Using the United Network for Organ Sharing (UNOS)/Organ Procurement and Transplantation Network (OPTN) database, we evaluated patient and graft survival after orthotopic liver transplantation for sarcoidosis between October 1987 and December 2007. We assessed the potential prognostic value of multiple demographic and clinical variables, and we also compared these patients to a case-matched group of patients with primary sclerosing cholangitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
0
30
0
6
Order By: Relevance
“…This adds to our recent publication on this subject when we found statistically worse outcomes (both graft and patient survival) for sarcoidosis patients when compared with other cholestatic diseases like PSC and PBC. 25 Previous studies, however, showed similar outcomes for these patient groups but these were small and selection bias remains a concern. 20,21 One possible reason for relatively poorer outcome of liver transplantation for these patients could be that sarcoidosis is a multi-organ disease with special predilection for vital organs.…”
Section: Discussionmentioning
confidence: 88%
“…This adds to our recent publication on this subject when we found statistically worse outcomes (both graft and patient survival) for sarcoidosis patients when compared with other cholestatic diseases like PSC and PBC. 25 Previous studies, however, showed similar outcomes for these patient groups but these were small and selection bias remains a concern. 20,21 One possible reason for relatively poorer outcome of liver transplantation for these patients could be that sarcoidosis is a multi-organ disease with special predilection for vital organs.…”
Section: Discussionmentioning
confidence: 88%
“…Most commonly, sarcoidosis is discovered in donor solid organ allografts in recipients with a history of sarcoidosis [73][74][75][76][77][78][79][80], presumably inducing a granulomatous response by the recipient's immune system [81]. One report of sarcoidosis presenting following bone marrow transplantation suggests that this susceptibility may depend on donor MHC haplotypes [82].…”
Section: Models Of Sarcoidosis Pathobiologymentioning
confidence: 99%
“…Les résultats de la transplantation hépatique au cours de la sarcoïdose sont satisfaisants mais sont moins bons qu'au cours des autres hépatopathies chroniques cholestatiques [32]. De même, les récidives sur greffon sont possibles et seront les principales causes de rejet et de décès chez les greffés [31,32].…”
Section: Discussionunclassified
“…De même, les récidives sur greffon sont possibles et seront les principales causes de rejet et de décès chez les greffés [31,32]. La splénectomie peut être aussi envisagée dans les atteintes spléniques réfractaires et/ou compliquées de la sarcoïdose [19].…”
Section: Discussionunclassified